Предмет: Алгебра,
автор: asdlkj29
с
13.15. Решите уравнение:
1) (x +10)(х - 9) - (х - 8) = 0;
2) (х + 11)(х + 9) - (х-3)(х + 40) = 0;
3) (x - 6)(7 + х) + (3 - x)(3 + х) = 0;
4) (x-4)(4 + х) - (1 - x)(9 - x) = 0.
Ответы
Автор ответа:
19
Объяснение:
1) (x+10)(x-9)-(x-8)=0
x²+x-90-x+8=0
x²-82=0
x²=82
x=±√82
2) (x+11)(x+9)-(x-3)(x+40)=0
x²+20x+99-(x²+37x-120)=0
x²+20x+99-x²-37x+120=0
20x-37x+99+120=0
219-17x=0
17x=219
3) (x-6)(7+x)+(3-x)(3+x)=0
7x+x²-42-6x+9-x²=0
x-33=0
x=33
4) (x-4)(4+x)-(1-x)(9-x)=0
4x+x²-16-4x-(9-x-9x+x²)=0
x²-16-9+10x-x²=0
10x=25
x=25/10
x=2,5
Похожие вопросы
Предмет: Английский язык,
автор: nurasylamangeldi78
Предмет: Английский язык,
автор: sabinkaaaaaaa
Предмет: История,
автор: Vilooolaa
Предмет: Математика,
автор: таир14
Предмет: Химия,
автор: sejtmuratov